Judicial Reform in China: Lessons from Shanghai - Gechlik, Mei Ying (Columbia Journal of Asian Law, 2005)
The rise of China has become an important factor in the global political, economic, and military balance of this century. While the international community welcomes a more prosperous China, it is deeply concerned about the potential threat of the communist country’s rise. To ease such concern and to respond to criticisms against the Chinese Communist Party’s (“CCP”) governance, Beijing has vowed to establish a “harmonious society of socialism” that features, along with other attributes, the rule of law, fairness, and justice. Unfortunately, courts in China have yet to exemplify the rule of law, fairness, and justice. Understanding that a dysfunctional justice system severely impairs governance, Beijing has taken a series of actions to reform China’s judiciary. In 1999, immediately after the CCP decided at the Fifteenth Party Congress to “promote judicial reform”, the Supreme People’s Court (“SPC”) announced a five-year reform plan to build a “fair, open, highly effective, honest, and well-functioning” judicial system. “Judicial fairness” was highlighted as the “essence” of judicial reform. Since then, gongzheng has always been the central theme, although Chinese leaders have coined various expressions to describe their judicial reform initiatives, including “fairness and efficiency”, “administering justice for the people”, and “fair judicature, serving the people wholeheartedly”.